Design and Testing of an Inter-Toothed, Self-Propelled Digger for Deep-Rhizome Chinese Herbal Medicines - Peng Wu; Wei Sun; Hucun Wang; Luhai Zhang; Petru A. Simionescu (Agronomy)
To address the challenges of digging deep-rhizome Chinese herbal medicines in northwest China’s hilly terrain, including difficulty, incompleteness, and herb damage, a specialized self-propelled digger with interlocking teeth has been developed. Designed for complex topography, small fields, and resistant soil, this digger provides an efficient and precise alternative to traditional methods. The prototype features in-place reverse differential steering, 360-degree digging capability, and minimized root and soil damage to promote future planting. Key components, including the digging mechanism, vibratory system, crawler chassis, hydraulic transmission system, and worm gear rotary hydraulic reducer, were analyzed and optimized through theoretical, graphical, and simulation studies using RecurDyn. Field tests demonstrated the digger’s effectiveness, achieving depths exceeding 600 mm with minimal herb damage and loss. The digger successfully navigated steep slopes and operated within noise regulations, surpassing industry standards, with less than 1.4% herb damage and a loss rate under 3%. The digger was capable of ascending gradients over 20° with driver noise levels below 92 dB. This innovative solution offers a valuable reference for developing specialized diggers for harvesting traditional Chinese medicinal materials in challenging conditions.